Cu6 Sn5 and Cu3 Sn intermetallics study in the Sn-40Pb/Cu system during long-term aging / Ramani Mayappan and Zainal Arifin Ahmad - Mayappan, Ramani; Ahmad, Zainal Arifin (Research Management Institute (RMI), 2010)
Replacing Sn-Pb solder with lead-free solder is a great challenge in the electronics industry. The presented lead-free solder is Sn based and forms two intermetallic species upon reaction with the Cu substrate, namely Cu6 Sn5 and Cu Sn. The growth of Cu6 Sn5 and Cu Sn intermetallics have been investigated with respect to Sn-40Pb/Cu solderjoints. The joints were aged under long-term thermal exposure using single shear lap joints and the intermetallics were observed using scanning electron microscopy. As-soldered solder joints exhibit a single Cu6 Sn5 phase, however after aging a Cu Sn layer below the Cu6 Sn5 is observed to manifest. The Cu6 Sn5 layer develops with a scalloped morphology, whereas the Cu Sn layer always develops an undulating planar shape in phase with the Cu6 Sn5. The C1I6Sn5 layer begins to transform from a scalloped- to a planar-shape as aging progresses in order to minimize the interfacial energy. The intermetallic layers exhibit a linear dependence on the square root ofaging time, which corresponds to diffusion-controlled growth. The activation energy for the growth of the CuSn, intermetallic layer has been determined to be 56.16 kJlmol.